Recommendations in pre-procedural imaging assessment for transcatheter aortic valve implantation intervention: Italian Society of Cardiology (SIC)–Italian Society of Medical and Interventional Radiology (SIRM) position paper part 1 (Clinical Indication and Basic Technical Aspects, Heart Team, Role of Echocardiography). Issue 4 (12th April 2022) - Pontone, Gianluca; Marano, Riccardo; Agricola, Eustachio; Alushi, Brunilda; Bartorelli, Antonio; Cameli, Matteo; Carrabba, Nazario; Esposito, Antonio; Faletti, Riccardo; Francone, Marco; Galea, Nicola; Golino, Paolo; et al.
Abstract : Non-invasive cardiovascular imaging owns a pivotal role in the preoperative assessment of patients for transcatheter aortic valve implantation (TAVI), providing a wide range of crucial information to select the patients who will benefit the most and have the procedure done safely. Although advanced cardiac imaging with cardiac computed tomography is routinely used for a detailed anatomic assessment before TAVI, echocardiography remains the first imaging modality to assess aortic stenosis severity and to provide essential functional information. This document results from the collaboration between the Italian Society of Cardiology (SIC) and the Italian Society of Medical and Interventional Radiology (SIRM), aiming to produce an updated consensus statement about the pre-procedural imaging assessment in patient for TAVI. The writing committee is composed of radiologists and cardiologists, experts in the field of cardiac imaging and structural heart diseases. Part 1 of the document, after a brief overview of the clinical indication and basic technical aspects of TAVI, will focus on the role of echocardiography in TAVI pre-procedural planning.